Variations in the Uptake of Routine Immunization in Nigeria: Examining Determinants of Inequitable Access. (1st January 2016) - Olorunsaiye, Comfort Z.; Degge, Hannah
Abstract : Globally, immunization prevents an estimated 2–3 million deaths among under-5 children, yet in Nigeria, only 25% of children ages 12–23 months are fully immunized. There are also marked disparities in the uptake of immunizations, largely attributable to the context within which families live and seek health care. The authors assessed the individual and state determinants of child immunization in Nigeria and used multilevel logistic regression to estimate the odds of full immunization among 5, 561 children aged 12–23 months, with their mothers clustered in the 36 states and the Federal Capital Territory (level 2). Findings indicate low immunization coverage rates overall: diphtheria, pertussis, and tetanus vaccine first dose (DPT1) = 49.8%, DPT3 = 38.2%, measles = 41.8%, and full immunization = 24.9%. There was also significant clustering of full immunization among states. The authors found that having a health card and receiving postnatal care within the first 2 months of life were positively associated with full immunization, as were maternal education, wealth, age, and ethnicity. At the state level, the proportion of employed mothers and those who received tetanus immunization before birth was positively associated with full immunization. The following barriers were negatively associated with full immunization: needing to obtaining permission, poor financial situation, and far distance to clinic. These findings call for state-specific targeting to address inequitable access to routine immunization in Nigeria.